Attitudes of the University of the Philippines Los Banos students toward physical fitness and exercise - Buan, Aivi R. (2014)
All schools, public or private, are required to establish Physical Education program for excellence, motivation for exercise and fitness and standard development. This should be given equal observation of results, system of conducts, beneficial treatments and proper attention. Students who by grades and levels participate in physical education class in school have the chance to develop a positive outlook towards health so as with the physical programs provided by their respective institutions. In equal vision of the same right as subject, Physical Education, according to the study, is special subject created through the government provision and constitutional mandatory efforts. So by type and ranking to the syllabus of school prospectus, this subject must be finished by a pupil/student in the same t procedure. Teachers as well as the students should consider the subject just like regular science and math courses in the classroom. The students must participate in whatever the Physical Education teacher is imparting to them should take the subject seriously or in good perspective.
Through a rigorous physical education course, students develop more the emotional and physical aspects of their personalities. This contribute to their abilities to cultivate teamwork, enhance fitness and develop hygienic awareness as well as in building camaraderie and sportsmanship. However, based on research and observation, it was shown that Physical Education is a subject that most students take for granted. They see the subject as a part of their recess or vacant time for relaxation. Furthermore, teachers found out that male and female students had the same attitude towards the subject.
Keywords: Physical fitness; Physical education